2008
DOI: 10.1089/jamp.2007.0662
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery through Nasal Cannulas: An In Vitro Study

Abstract: In most circumstances, a nasal route for the delivery of pulmonary aerosol medications is rarely considered; however, in specific instances, this route may be quite useful. Consider, for example, the delivery of aerosol treatments during humidified high-flow nasal cannula use in pediatric critical care, or continuous aerosol delivery via cannula for medications with short durations of action. The goal of this study was to evaluate the potential for delivering aerosols via nasal cannula through in vitro studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
109
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 17 publications
17
109
2
1
Order By: Relevance
“…Another in vitro study demonstrated that 18 -26% of the medication dose was delivered using a pediatric nasal cannula, and the authors concluded that aerosolized medications can be effectively delivered via HFNC. 18 In conclusion, although many in vitro studies exist, few clinical reports of aerosolized bronchodilator administration via HFNC and the Aerogen Solo exist. We report 5 cases of infants with bronchiolitis who were given ␤-agonist bronchodilators via HFNC and the Aerogen Solo.…”
Section: Discussionmentioning
confidence: 99%
“…Another in vitro study demonstrated that 18 -26% of the medication dose was delivered using a pediatric nasal cannula, and the authors concluded that aerosolized medications can be effectively delivered via HFNC. 18 In conclusion, although many in vitro studies exist, few clinical reports of aerosolized bronchodilator administration via HFNC and the Aerogen Solo exist. We report 5 cases of infants with bronchiolitis who were given ␤-agonist bronchodilators via HFNC and the Aerogen Solo.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the study by Bhashyam et al 30 was to evaluate the potential for delivering aerosols by a nasal cannula by in vitro studies of aerosol output and particle size. They evaluated a mesh nebulizer placed downstream of a heated-humidification system and a nasal cannula.…”
Section: Aerosol Delivery During Hfncmentioning
confidence: 99%
“…The first study was conducted by Bhashyam et al (2008), researchers at the University of Pittsburgh in Pennsylvania. This was an in-vitro study of aerosol size and output designed to evaluate the possibility of delivering aerosols through nasal cannula.…”
Section: Aerosol Delivery Via Ncpap Systemsmentioning
confidence: 99%
“…While research comparing aerosol drug delivery through HFNC, bubble CPAP, and SiPAP is lacking, only two studies have assessed the effectiveness of aerosol drug delivery through HFNC (Ari et al, 2011;Bhashyam et al, 2008). Moreover, only one study has compared aerosol delivery through two different CPAP systems, yet that study included V-CPAP and B-CPAP (Zweifel, 2010).…”
Section: Effect Of Hfnc and Cpap Systems On Aerosol Deliverymentioning
confidence: 99%
See 1 more Smart Citation